1981
DOI: 10.1021/bi00507a023
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance characterization of aromatic residues of .alpha.-lactalbumins. Laser photochemically induced dynamic nuclear polarization nuclear magnetic resonance studies of surface exposure

Abstract: The alpha-lactalbumins are involved as modifier proteins in lactose biosynthesis. Lactalbumins from different mammalian species are cross-reactive with the galactosyltransferases from others because of their homologous primary and tertiary structure. We have studied the surface exposure of several alpha-lactalbumins (bovine, goat, human, guinea pig, and rabbit) by the laser photo-CIDNP technique, an NMR method which measures the access of a photoexcited flavin dye to surface exposed Tyr, Trp, and His residues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 36 publications
6
38
0
Order By: Relevance
“…Above 320K, new emissive peaks are progressively observed at 7.12 (320 K), 6.75 (327 K) and at 6.53 ppm (335 K). Surprisingly, the spectrum at 335 K is similar to that obtained previously by Kaptein and Berliner at the same pH but at room temperature (Berliner and Kaptein, 1981). A close investigation showed that the protein used in that study (no.…”
Section: Resultssupporting
confidence: 87%
“…Above 320K, new emissive peaks are progressively observed at 7.12 (320 K), 6.75 (327 K) and at 6.53 ppm (335 K). Surprisingly, the spectrum at 335 K is similar to that obtained previously by Kaptein and Berliner at the same pH but at room temperature (Berliner and Kaptein, 1981). A close investigation showed that the protein used in that study (no.…”
Section: Resultssupporting
confidence: 87%
“…Galactosyl transferase was isolated as previously described (12). Galactosyl transferase assays formatted for 96-well plates were performed as described by Fitzgerald et al (13).…”
Section: ␣-Lactalbumin-stimulated Lactose Synthase Activitymentioning
confidence: 99%
“…The basic process involves a radical pair formation step by reversible H-atom transfer (Muszkat and Weinstein, 1976) from a peptide side chain to a dye triplet. Protein CIDNP has been applied to peptides and proteins (see, e.g., Muszkat, 1977;Muszkat et al, , 1982Muszkat et al, , 1983Muszkat et al, , 1984aGitlin et al, 1989;Berliner and Kaptein, 1981;Berliner et al, 1990). It was applied some time ago in the study of the conformations of elapid snake cr-neurotoxins (Muszkat et al, 1984b;Muszkat, 1993) and of the membranotoxins (Muszkat et al, 1984b).…”
Section: Discussionmentioning
confidence: 99%
“…The prime experimental approach we use in these studies is protein CIDNP spectroscopy (photochemically induced dynamic nuclear polarization) (see, e.g., Muszkat, 1977;Muszkat et al, , 1982Muszkat et al, , 1983Muszkat et al, , 1984aBerliner and Kaptein, 1981;Berliner et al, 1990), which provides detailed structural and accessibility information, and ensures enhanced sensitivity specific for the CIDNP active side chains. Myotoxin a damages the sarcoplasmic reticulum (SR) membrane by associating with its two components, the Ca 2 § ATPase and the 53GP glycoprotein (Volpe et al, 1986;Utaisincharoen et al, 1991;Tu et al, 1992).…”
Section: Introductionmentioning
confidence: 99%